THE NEGATIVE EFFECT OF LONG-TERM CHEMOTHERAPY ON HEART FUNCTION - Jakhongir A. Sherov; Lola Dj. Sultanova (Central Asian Journal of Medicine, 2023)
Recovery from chemotherapy can take place in different ways for different patients and depends on several factors, such as the type and dose of chemotherapy drugs used, the duration of treatment, as well as the general state of health and the level of physical fitness of a person. Typically, the immediate side effects of chemotherapy may persist for several days or weeks after treatment and may include fatigue, nausea and vomiting, hair loss, mouth ulcers, and changes in appetite or taste. These side effects can be managed with medications, dietary changes, and other supportive treatments, and they usually go away over time. There may also be long-term side effects of chemotherapy, such as nerve damage, hearing loss and an increased risk of infection, which may persist for months or years after treatment. For those who have received chemotherapy, it is important to monitor these potential long-term effects and receive appropriate follow-up treatment.